CALCULATION OF REINFORCED CONCRETE INSULATED PIPES - Zhanybekova K.M., Жаныбекова К.М. (Рroblems of engineering and professional education, 2023)
Inmodernconditions, the useof underground space-this is a verytopical issueespecially in big cities. This article discusses on underground and buried structures. Showing different calculation schemes of buried structures and methods of their calculation.